The Chromosomes of three species of the Nasonia complex (Hymenoptera, Pteromalidae). - Gokhman, Vladimir E.; Westendorff, Magdalene (Contributions to Entomology = Beiträge zur Entomologie, 2000)
The karyotypes of three sibling species, Nasonia vitripennis (Walker, 1836), N. longicornis Darling, 1990 and N. giraulti Darling, 1990 were examined, the latter two species for the first time. All species have chromosome numbers of n=5 and 2n=10, their chromosomes being metacentric. The distribution of constitutive heterochromatin also appears to be similar in the genus Nasonia Ashmead, 1904. However, statistical karyotypic differences between studied species were revealed using chromosome morphometrics. These data are consistent with the order of divergence in the Nasonia complex found on the basis of molecular studies.